Developing Linear and Rotational Pathways For Self-Access Center - Agnes Santi Widiati; Aniek Setiawaty; Davy Budiono (Widya Mandala Surabaya Catholic University, 2010)
Self-Access Center is a system which makes materials available for its users so that they can choose to work as they wish. As a bank of materials, it gives freedom for the users to roam in the forest of Self- Access and explore various learning materials with or without teacher's assistance. In this self-directed situation, users have more autonomy and responsibility on their own learning. However, in such situation, they may lose directions in choosing the materials. Therefore users need pathways as a guideline to direct themselves to choose the appropriate materials. Pathways have the capacity to provide routes to make connections between materials so that the real power of self-access is unlocked. Furthermore they direct the users not just through one text-book or worksheet, but through hundreds or thousands of them. The creation of entire webs of such pathways can be developed through rotational and linear types of pathways. This workshop is intended to give the Self- Access staff and English teachers some possible ways in developing Self- Access rotational and linear pathways for their learners.